Exploring Functional Impairment in Light of Prolonged Grief Disorder: A Prospective, Population-Based Cohort Study - Nielsen, Mette Kjaergaard; Christensen, Kaj Sparle; Neergaard, Mette Asbjoern; Bidstrup, Pernille Envold; Guldin, Mai-Britt (Frontiers in Psychiatry, 2020)
Background Functional impairment is an essential part of the ICD-11 diagnostic criteria for prolonged grief disorder (PGD) and refers to the negative impact on everyday life, including inability to maintain the usual level of functioning. We aimed to assess the extent of overall functional impairment, role limitation due to emotions and impaired social functioning (Short Form survey-36 subscales (SF-36)) prior to and after bereavement and to explore associations with PGD. Method Relatives of terminally ill patients (n=1622) completed a questionnaire before and after bereavement. The questionnaire assessed the proportion reporting overall functional impairment (PG item) and functional impairment aspects using mean scores of the SF-36 subscales emotional role limitation and social functioning (0(worst) to 100(best)). We analyzed associations between PGD (PG-13 criteria) and functional impairment prior to bereavement using logistic regression models adjusted for age, gender, personal relation, education, time interval to patient’s death, and pre-loss grief. Results In total, 51% reported overall functional impairment prior to bereavement, 27% reported functional impairment at six months after bereavement, and 19% reported functional impairment at three years after bereavement. Mean emotional role limitation was 47.5 (95%CI: 45.4-49.7) before bereavement, increasing to 77.4 (95%CI: 75.7-79.0) at three years after bereavement, compared to 85.1 (95%CI: 77.6-92.6) in the general population. Mean social functioning increased gradually and equaled the general population mean at three years after bereavement. In those with overall functional impairment, PGD was present in 26% at six months after bereavement and in 11% at three years after bereavement. Pre-bereavement measures of emotional role limitation and social functioning and selected items in the scales were associated with PGD at six months after bereavement. Discussion Overall functional impairment was very prevalent and was reflected in low assessments of daily activities and social functioning compared to the general population. Hence, functional impairment was significant in bereavement and pre-bereavement functioning was associated with PGD. Future studies should investigate if maintaining daily activities and social functioning prior to bereavement may be a target in early support services. Also, studies are needed to further explore the role of functional impairment in bereavement outcomes such as depression.